Political hazards, experience, and sequential entry strategies: the international expansion of Japanese firms, 1980–1998 - Delios, Andrew; Henisz, Witold J. (Strategic Management Journal, 2003)
Abstract We find support for the role of experiential learning in the international expansion process by extending the stages model of internationalization to incorporate a sophisticated consideration of temporal and cross‐national variation in the credibility of the policy environment. Using a sample of 3857 international expansions of 665 Japanese manufacturing firms, we build on the concepts of uncertainty and experiential learning, to show that firms that had gathered relevant types of international experience were less sensitive to the deterring effect of uncertain policy environments on investment. One implication of our results is that research on international strategy should emphasize understanding the political institutions that constrain or enable political actors, just as entry mode research has done. A second implication is that research in the stages model of internationalization should give the same weight to the policy environment as a source of uncertainty to a firm, as it has given to cultural, social and market institutions. Copyright © 2003 John Wiley & Sons, Ltd.